2012
DOI: 10.1007/s10509-012-1308-y
|View full text |Cite
|
Sign up to set email alerts
|

Discovering protostars and their host clusters via WISE

Abstract: A hybrid JHK s − W 1 W 2 W 3 W 4 high-spectral index (α) selection scheme was employed to identify (sub)clusters of class I/f candidate protostars (YSOs) in WISE observations (the Wide-Field Infrared Survey Explorer). n > 10 4 candidate YSOs were detected owing to WISE's advantageous all-sky spatial coverage, and a subsample (n ∼ 200) of their heavily-obscured host (sub)clusters were correlated with the Avedisova (2002) and Dias et al. (2002) catalogs of star-forming regions. Forthcoming observations from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…We found that only 5 new GLIMPSE clusters (they are indicated in Table 2) are associated with objects from the published list by Majaess (2013), in particular these 5 clusters are contained within the corresponding objects identified by Majaess (2013), which cover a much larger area. Due to the coarser angular resolution of WISE data with respect to GLIMPSE data, the typical stellar densities in our ECs are probably too high to make all the individual members detectable at the WISE resolution, and consequently they are hidden in the Majaess (2013) YSO selection.…”
Section: New Search For Ecs In Glimpsementioning
confidence: 89%
“…We found that only 5 new GLIMPSE clusters (they are indicated in Table 2) are associated with objects from the published list by Majaess (2013), in particular these 5 clusters are contained within the corresponding objects identified by Majaess (2013), which cover a much larger area. Due to the coarser angular resolution of WISE data with respect to GLIMPSE data, the typical stellar densities in our ECs are probably too high to make all the individual members detectable at the WISE resolution, and consequently they are hidden in the Majaess (2013) YSO selection.…”
Section: New Search For Ecs In Glimpsementioning
confidence: 89%
“…In the recent compilation of stellar clusters, updated to August 2011 of all Galactic star cluster catalogs (e.g., Dias et al 2002;Mercer el at 2005;Dutra et al 2003;Bica et al 2003;Borissova et al 2011), Morales et al (2013) counted 2247 clusters visible in the optical and 1950 and 197 cluster candidates found in the near-and mid-infrared, respectively. Since then, Solin et al (2012Solin et al ( , 2014, Majaess (2013), and Zasowski et al (2013) reported 137; 88; 229 and 20 new embedded cluster candidates in the UKIDSS GPS, VVV, WISE, and Spitzer GLIMPSE-360 areas. This increases the number of near-infrared cluster candidates to 2404.…”
Section: Cluster Search and Methods Of Analysismentioning
confidence: 99%
“…Majaess (2013) has also made a significant contribution on young clusters (see also, Bica et al 2003a,b;Lada & Lada 2003;Mercer et al 2005;Froebrich, Scholz & Raftery 2007;Borissova et al 2011;Solin, Haikala & Ukkonen 2014).…”
Section: Introductionmentioning
confidence: 93%